2020
DOI: 10.1016/j.cub.2020.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Extranuclear Structural Components that Mediate Dynamic Chromosome Movements in Yeast Meiosis

Abstract: Highlights d Mps2 connects the LINC complex to the cytoskeleton d Myo2 interacts with Mps2 and connects the telomer to cytoskeleton actin filaments d Csm4 works together with Mps2 and Myo2 to regulate rapidprophase movements

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 65 publications
3
43
1
Order By: Relevance
“…We note that a recent work also suggests that Mps2 acts as a member of the t-LINC (Lee et al, 2020). In budding yeast, the combined action of Mps2 and Csm4 is needed to carry out the function of the canonical KASH protein at the t-LINC.…”
Section: Reconstituted T-linc Can Tether Telomeresmentioning
confidence: 60%
“…We note that a recent work also suggests that Mps2 acts as a member of the t-LINC (Lee et al, 2020). In budding yeast, the combined action of Mps2 and Csm4 is needed to carry out the function of the canonical KASH protein at the t-LINC.…”
Section: Reconstituted T-linc Can Tether Telomeresmentioning
confidence: 60%
“…In contrast, the meiotically induced Csm4 protein forms LINC complexes with Mps3 along the NE. A recent report has shown that, during meiotic prophase, Mps2 also interacts with Csm4 at the NE mediating the coupling with the Myo2 microfilament motor associated to the actin cytoskeleton (Lee et al, 2020). During meiotic prophase, telomeres are anchored to the nucleoplasmic N-terminal domain of Mps3 by the mediation of the meiosis-specific Ndj1 protein.…”
Section: Introductionmentioning
confidence: 99%
“…whereas Csm4 is a meiosis-specific ONM protein (Conrad et al, 2007;Kosaka et al, 2008;Wanat et al, 2008), which interacts with a unique class of KASH protein, Mps2 (Chen et al, 2019;Lee et al, 2020). Second, the formation of actin cables is specifically induced in the cytoplasm of meiotic cells (Koszul et al, 2008;Taxis et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Third, NE dynamics including NE remodeling and movement occur prominently in meiotic prophase I (Conrad et al 2007;this paper). NE remodeling is accompanied by NE localization of a yeast SUN-domain protein, Mps3/Nep98 (Conrad et al, 2007) as well as Mps2 (Lee et al, 2020). In mitosis, Mps3 and Mps2 predominantly localizes to SPB as a component of the halfbridge as well as SPB-interacting network (SPIN) (Chen et al, 2019) and play an essential role in SPB duplication (Jaspersen et al, 2002;Nishikawa et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation